Identificação e clonagem de genes espécie-específicos de Leishmania infantum para expressão piloto de proteínas recombinantes com potencial para o diagnóstico de Leishmaniose Visceral - Steffler, Joselma Maria Dias (2023)
Leishmaniasis is a public health problem observed in several countries, being considered by the World Health Organization (WHO) one of the 10 neglected tropical diseases. It is caused by Leishmania parasites that affect both humans and animals. Leishmaniasis has three clinical manifestations, Cutaneous Leishmaniasis (CL), Mucocutaneous Leishmaniasis (MCL) and Visceral Leishmaniasis (VL), the latter is the most severe form of the disease. The symptomatology of VL is nonspecific and includes fever, hepatomegaly, splenomegaly, diarrhea, weight loss and pale mucous membranes. Early diagnosis decreases VL morbidity and mortality rates, which can reach up to 90% if left untreated. Its diagnosis is done through the association of clinical signs, epidemiological aspects combined with parasitological and/or serological tests. A specific diagnostic test with high sensitivity is very important to avoid cross-reactions with other infectious and parasitic diseases with similar symptoms. Considering that current serological tests present variable effectiveness, studies to reach a more accurate diagnosis is necessary. This precision can be achieved using antigens that provide specificity in parasite detection. Thus, the aim of this study were to perform in silico predictions of potential antigens by searching species-specific genes in genome of Leishmania infantum using Bioinformatics tools, such as BLAST/NCBI, BepiPred, UniProt, CDD and AlphaFold. The most promising candidate genes obtained in the in silico analysis step were isolated from the genome of HUUFS14 L. infantum strain, cloned in pET28a vector and expressed as recombinant protein in bacterial system (Escherichia coli). Afterwards, three genes of interest, LINF_070006600, LINF_310021300 and LINF_310031700 were submitted to recombinant protein expression test. The products of these genes are hypothetical proteins and unknow function, with a molecular weight of 14, 15 and 36 kDa respectively. Possibly, they act in the extracellular environment, because the presence of a signal peptide (LINF_070006600) and a transmembrane domain site (LINF_310021300 and LINF_310031700) were identified. Only the expression of the LINF0700 recombinant protein was observed, but with a size above the expected. This work was important for identifying genes exclusive to L. infantum, and the expressed recombinant protein could be used in future studies to evaluate new antigens for serological diagnosis of visceral leishmaniasis.